2018
DOI: 10.1080/1478422x.2018.1446582
|View full text |Cite
|
Sign up to set email alerts
|

The replacement of chromate by molybdate in phosphoric acid-based etch solutions for aluminium alloys

Abstract: Corrosion inhibition of aluminium alloys in the acidic solutions is important in the aluminium finishing industry (stripping solutions for anodic films). Sodium molybdate is a potential replacement for chromate-containing species used in the stripping solutions. It was tested as the corrosion inhibitor of 2024 aluminium alloy in orthophosphoric acid solutions. A corrosion rate of the alloy as a function of an initial concentration of sodium molybdate and temperature was determined by using gravimetric and gaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…It can be concluded that Al 2 Cu, significantly enhancing dissolution of the matrix and adjacent intermetallics, determines the corrosion behaviour of the studied alloy. This behaviour can be compared to Al-Cu cast alloys, 2024 [5] 7075 [7] the dendrites increases outward from their centre. [24] Unfortunately, the corrosion mechanism of these alloys was rarely studied in acidic solutions.…”
Section: Uninhibited Solutionmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be concluded that Al 2 Cu, significantly enhancing dissolution of the matrix and adjacent intermetallics, determines the corrosion behaviour of the studied alloy. This behaviour can be compared to Al-Cu cast alloys, 2024 [5] 7075 [7] the dendrites increases outward from their centre. [24] Unfortunately, the corrosion mechanism of these alloys was rarely studied in acidic solutions.…”
Section: Uninhibited Solutionmentioning
confidence: 99%
“…The first one is insufficient corrosion protection of aluminium alloys, especially with a high content of copper. [ 5 ] This requires further studies of corrosion behaviour of intermetallics, existing in aluminium alloys, in H 3 PO 4 –Na 2 MoO 4 system. The second one is the precipitation of an insoluble Mo‐containing salt on the metallic surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heteropolyoxoanions can be formed by about 60 elements on the periodic [24,[27][28][29]. Interestingly, iso-and heteropolyoxomolybdates also decrease the dissolution rate of anodic coatings in solutions of orthophosphoric acid [30].…”
Section: Introductionmentioning
confidence: 99%